2014
DOI: 10.1186/2050-7771-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the source of elevated hepatocyte growth factor levels in multiple myeloma patients

Abstract: BackgroundHepatocyte growth factor (HGF) is a pleiotropic cytokine which can lead to cancer cell proliferation, migration and metastasis. In multiple myeloma (MM) patients it is an abundant component of the bone marrow. HGF levels are elevated in 50% of patients and associated with poor prognosis. Here we aim to investigate its source in myeloma.MethodsHGF mRNA levels in bone marrow core biopsies from healthy individuals and myeloma patients were quantified by real-time PCR. HGF gene expression profiling in CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…MM cells directly stimulate OC formation by releasing a variety of proinflammatory OCactivating factors (OAFs), including receptor activator of nuclear factor κB (NF-κB) ligand (RANKL), macrophage inflammatory protein 1α (MIP-1α), tumor necrosis factor α (TNFα), interleukin (IL)-3, IL-6, parathyroid hormone-related protein (PTHrP), and hepatocyte growth factor (HGF) (Choi et al 2000;Frassanito et al 2001;Giuliani et al 2004;Lee et al 2004;Cafforio et al 2014;Rampa et al 2014). Moreover, MM cells indirectly increase osteoclastogenesis via interactions with BMSCs, osteocytes, and resident T cells.…”
Section: Mechanisms Of Bone Destruction In Mmbdmentioning
confidence: 99%
“…MM cells directly stimulate OC formation by releasing a variety of proinflammatory OCactivating factors (OAFs), including receptor activator of nuclear factor κB (NF-κB) ligand (RANKL), macrophage inflammatory protein 1α (MIP-1α), tumor necrosis factor α (TNFα), interleukin (IL)-3, IL-6, parathyroid hormone-related protein (PTHrP), and hepatocyte growth factor (HGF) (Choi et al 2000;Frassanito et al 2001;Giuliani et al 2004;Lee et al 2004;Cafforio et al 2014;Rampa et al 2014). Moreover, MM cells indirectly increase osteoclastogenesis via interactions with BMSCs, osteocytes, and resident T cells.…”
Section: Mechanisms Of Bone Destruction In Mmbdmentioning
confidence: 99%
“…Activation of the HGF/c-MET pathway has been evaluated using serum or plasma HGF, because HGF is expelled from tumor cells to the extracellular matrix and blood plasma by a paracrine mechanism [ 12 ]. Increased serum HGF (sHGF) has been reported to be a negative prognostic marker in various malignancies including colorectal cancer, gastric cancer [ 13 15 ], prostate cancer [ 16 ], ovarian cancer [ 17 ], breast cancer [ 18 , 19 ], glioma[ 20 ], melanoma [ 21 ], and multiple myeloma [ 22 , 23 ]. Recently, a Spanish group reported that high sHGF in patients with SCLC predicts poor outcome and epithelial-mesenchymal transition (EMT) change in the tumor [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In association with basic fibroblast growth factor, vascular endothelial growth factor, and soluble syndecan‐1, HGF significantly increases angiogenic activity within myeloma bone marrow, supporting the survival and regeneration of malignant PCs (Gherardi, ; Sezer et al, ; Andersen et al, ). High concentrations of HGF in MM sera are produced by myeloma cells and associated with short‐term responses to therapies and early relapses of MM (Seidel et al, ; Rampa et al, ).…”
Section: Introductionmentioning
confidence: 99%